Stability of snow cover on the territory of Russia in relation to climate change - A. N. Krenke; E. A. Cherenkova; M. M. Chernavskaya (Лëд и снег, 2015)
The change of the snow cover stability characteristics over the Russian territory including regional and seasonal features of this change in the modern warming period of 1991–2008 in comparison with the period 1961–1990 are investigated in the paper using the data of 223 meteorological stations. Features of the snow cover regime related to teleconnection indices change of the North Atlantic Oscillation (NAO) and the West Pacific (WP) one are analyzed.Opposite tendencies of changes of the snow period duration were observed in most regions of Russia in each of the decades (1991–2008) in comparison with 1961–1990. Differently directed regional changes of the number of days without snow and interruption in snow cover were identified for each of the seasons in periods of intense warming in recent years compared to the baseline thirty years. Similar tendencies of seasonal changes of the number of days with snow depth more than 50 cm were observed in two decades in comparison with 1961–1990. The largest changes occurred in the winter and spring seasons. The spatial distribution of changes of the number of days with snow depth more than 50 cm also demonstrates the same tendency in the years with positive phase of the NAO and WP compared with the years of negative phase.